THE THE EFFECT OF CAPITAL TURNOVER, CURRENT RATIO AND FIRM SIZE WORKING ON PROFITABILITY IN THE MANUFACTURING COMPANY OF THE BASIC AND CHEMICAL INDUSTRY SECTORS LISTED IN INDONESIA STOCK EXCHANGE (BEI) PERIOD 2014-2017 - Sinaga, Risdayanti; Marbun, Betti Sulastri; Sianturi, Johannes R; Sitorus, Jessy Safitri (2020)
This research was held to examine the effect of working capital turnover, current ratio and firm size on profitability partially or simultaneously on manufacturing companies basic and chemical industry listed in Indonesia Stock Exchange in 2014-2017. The research was conducted with multiple linear regression analysis methods and hypothesis testing using the SPSS program. The overall population in this study were 69 companies and the sample were 27 companies with 108 data. The research showed that partially, (1) working capital turnover has a positive and significant effect on profitability, (2) current ratio has a positive and significant on profitability, (3) firmsize do not have a positive significant effect on profitability, (4) simultaneously, working capital turnover, current ratio, and firm size have a positive and significant on profitability.